2015
DOI: 10.5487/tr.2015.31.1.025
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in the Metabolism of Toluene: Comparisons between Korean and Foreign Workers Exposed to Toluene

Abstract: The objectives of this study were to investigate the individual characteristics, lifestyle habits, exposure levels, and genetic diversity of xenobiotic-metabolizing enzymes involved in toluene metabolism in Korean and foreign workers exposed to toluene at a manufacturing plant. This study was conducted to determine the effects of culture or ethnicity on toluene metabolism. The results showed that blood and urinary toluene concentrations were dependent on the level of exposure to toluene. We analyzed the correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…This result suggests that the genetic polymorphisms CYP2E1*5 and null/active GSTM1 were associated with the detoxification of styrene. In contrast, previous reports found that neither the genotypes of xenobiotic metabolizing enzymes nor lifestyle habits (smoking, drinking, and exercise) significantly affected the metabolism of xenobiotic including styrene (15 , 18) . Therefore, multiple logistic regression analysis was performed with the genetic polymorphisms of styrene-metabolizing enzymes and these lifestyle habits as dependent variables and styrene metabolites as independent variables.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…This result suggests that the genetic polymorphisms CYP2E1*5 and null/active GSTM1 were associated with the detoxification of styrene. In contrast, previous reports found that neither the genotypes of xenobiotic metabolizing enzymes nor lifestyle habits (smoking, drinking, and exercise) significantly affected the metabolism of xenobiotic including styrene (15 , 18) . Therefore, multiple logistic regression analysis was performed with the genetic polymorphisms of styrene-metabolizing enzymes and these lifestyle habits as dependent variables and styrene metabolites as independent variables.…”
Section: Discussioncontrasting
confidence: 70%
“…To analyze the concentration of blood styrene, 1 mL blood was collected from each subject and placed in a 20-mL headspace injection vial. The stopper was immediately replaced and a gas chromatograph/mass selective detector with a headspace sampler (Hewlett-Packard 7694 headspace sampler/6890 GC/5793 Mass Selective Detector, Agilent Technologies, Santa Clara, CA, USA) was used for the determination according to Kim et al (18) . The concentration of urinary styrene was also determined with this system according to Kim et al (18) .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas station workers with high toluene exposure have lower glutathione concentrations compared to the control group 21,22 . A research conducted in Korea showed that there was a significant relationship between toluene metabolism and glutathione 23 . However, studies conducted on mice given organic solvent for 3 days showed that toluene did not affect the amount of glutathione in the body 24 .…”
Section: Relationship Of Toluene Safe Duration (Hours/ Day) and Glutathione Concentrationmentioning
confidence: 99%
“…Preliminarily, it is worth emphasizing the presence of compounds that can be associated with the smoking habit. This is the case with p-cresol and benzyl alcohol, two compounds that can be obtained from toluene [21][22][23], which is one of the major components of tobacco smoke [24]. In fact, the levels of both compounds were strongly related, as deduced from their relative concentration variability represented in the mean plots.…”
Section: Biological Relevance Of the Compounds Involved In The Panelsmentioning
confidence: 99%